The feeling of hope in cancer patients: an existential analysis - Catarina Aparecida Sales; Marissa da Silva Cassarotti; Kelly Cristine Piolli; Laura Misue Matsuda; Julia Wakiuchi (Universidade Federal do Ceará, 2014)
This study aimed at unveiling the feeling of hope in people who experience cancer in their existence. Qualitative study based on Heidegger's phenomenology, performed with eight cancer patients assisted in a philanthropic organization, between December 2013 and February 2014, in a northwestern city in Paraná, Brazil, using the following guiding question: "How do you perceive the feeling of hope at this time in your life?" The analysis resulted in the ontological themes: searching for hope in dealing with cancer, and experiencing feelings of hope and despair in being with others. Patients revealed mixed feelings, going from the lack of hope at the time of diagnosis to a rekindling of hope, as well as those who never lost the will to live. We conclude that living with cancer causes extreme feelings; and hope emerges as a feeling capable of influencing and causes an expressive impact in coping with that.